Retirement and Voluntary Work Provision: Evidence from the Australian Age Pension Reform - Rong Zhu (Institute of Labor Economics (IZA), 2021)
This paper examines the empirical link between retirement and the supply of volunteer labor, using panel data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey. To identify the causal impact, we exploit a major reform of the Australian Age Pension which has significantly changed the retirement incentives of older people. We find positive and significant effects of retirement status on the voluntary work provision of older men and women. Longer time spent in retirement increases the unpaid labor supply of women, while there is no such evidence for men. We further find evidence of intra-household retirement externalities: older people's retirement impacts positively on the volunteer behavior of their family members. Our findings suggest that the Australian Age Pension reform aiming at working life prolongation has led to an unintended shrinkage of the volunteer workforce.
Keywords: H55; J22; J26; 330; retirement status; retirement duration; voluntary work; pension reform